Analisa Bahasa Bentuk Pada Desain Karakter Film Animasi “Spirited Away” - Pratiwi, Wilsa (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2024)
Creating character designs requires several stages in the process, and one of the knowledge that a designer must have is about shape language. The use of form language to make character designs easier for the audience to understand. Form language is a form of communication with certain meanings to create the desired character. Studio Ghibli is a popular animation studio known in various countries, one of the animated films made by Ghibli which has unique and iconic characters is